Application of Rhizobium Inoculum and Plant Population on Nodulation and Productivity of Edamame (Glycine max (L.) Merr.) - Rochman, Fajar; Rahmadi, Rizky; Sari, Evi Yunita (Politeknik Negeri Bengkalis, 2024)
Root nodulation is a crucial process for legumes, including edamame (Glycine max (L.) Merr.), as it enablesbiological nitrogen fixation, enhancing nitrogen availability for plant growth. The implementation of Rhizobiuminoculum has been demonstrated to reduce the necessity for synthetic fertilizers, thereby enhancing the health and yieldof the plants in question. Furthermore, optimal plant population management ensures adequate access to light, water, andnutrients, maximizing productivity. The combination of Rhizobium inoculation and population management represents acrucial strategy for enhancing the productivity and sustainability of legume crops, such as edamame. This study examinesthe impact of Rhizobium inoculation and plant population management on the nodulation and productivity of edamame.The research was conducted using a randomized block design, with two factors: the application of Rhizobium(Bradyrhizobium japonicum) at two levels (without inoculation and with inoculation) and plant spacing (20 x 15 cm and20 x 30 cm). Each treatment was replicated five times. The observed parameters included number of root nodulations,plant height, leaf area, leaf greenness, number of filled and empty pods, weight of filled and empty pods, wet weight, and100 seed weight. The data were subjected to analysis of variance, followed by Duncan's Multiple Range Test. Thefindings indicated that Rhizobium inoculation markedly enhanced root nodulation, with the 20 x 15 cm spacing inconjunction with inoculation yielding the highest total nodulation, number and wight filled pods, wet weight, and 100seed weight.